Climate change in the southern Amazonian Tropical Forest assessed by dendrochronological multiproxy - Ortega Rodríguez, Daigard Ricardo (2023)
Climate change driven by global warming, which in turn is exacerbated by deforestation (among other anthropic factors) affects the balance and services of Amazonian ecosystems. The southern Amazon basin is one of the regions most at risk of suffering the effects of climate changes and reaching a tipping point for its ecosystems to shift to non-forested areas. One of the ways to analyze how these changes can affect forests is through the indirect records obtained with dendrochronological analyses. These annual resolution records are an alternative to the scarce observational data and enable the climatic and environmental reconstruction of forest ecosystems. Although in the Neotropical region trees of different species have been identified as potential for dendrochronological studies, there are still few places with long-term tree-ring series and applied for the interpretation of climate variation. The main objective of this work is to study the response of trees to local and regional climate variation through dendrochronological multiproxy. Species with dendrochronological potential (especially Cedrela fissilis Vell.) occurring in the Jamari National Forest in the state of Rondônia, in the southern region of the Amazon basin, were analyzed to meet this main objective. The results of the analyzes are presented in three chapters. In Chapter I, the formation of growth rings of 12 species of tropical trees was analyzed through the relationships between anatomical characteristics and complementary physical (wood density) and chemical (S, K, Ca and Mn distribution) parameters, evaluated by X-ray densitometry and fluorescence techniques, respectively. In Chapter II, ring-width chronologies of Cedrela fissilis Vell (1875 to 2018), Hymenaea courbaril L. (1840 to 2018) and Peltogyne paniculata Benth. (1910 to 2018) were constructed and verified its annuality by the Post-AD 1950 14C analysis. In Chapter III, long-term chronologies of ring width, wood density, chemical elements (S and Ca) and stable oxygen isotope (δ18O) of Cedrela fissilis Vell. were constructed to understand local and regional climate variability; the long and short term response of growth and wood density of Cedrela fissilis Vell to the effects of extreme drought years for the period 1970-2018 was also analyzed. The present study shows that the multiproxy approach can be used to improve the definition and characterization of growth rings; for highly reliable reconstructions of atmospheric and hydroclimatic variability over the Amazon basin and for improving understanding of the long- and short-term responses of growth to climate change, specifically droughts. Altogether, this approach opens new perspectives for dendrochronological studies and their applications in the tropics.